Development and characterization of banana (Musa acuminata) pseudostem juice. - Palabrica, Florey Anne M.
Banana pseudostem is one of the by-products of banana farming. It is an underutilized resource that has a potential to be processed as a food, particularly as juice. The aim of this study was to develop juice from banana pseudostems. The formulated juice was characterized through physico-chemical analyses, namely pH, TA, and TSS; microbiological analysis through TPC; and, sensorial analyses, during storage (7 days) at ambient (29-320C) and chilled (9-110C) conditions. The pH of the banana pseudostem juice after 7 days of storage at chilled and ambient conditions ranged from 7.73 to 7.09 and 4.90, respectively. Analysis for the TA (% gsllic acid) of the juice samples showed that after 7 days of storage, the values increased from 0.0705% to 0.2267% and 1.9627% juices stored at chilled and ambient conditions, respectively. The TSS of the samples remained constant at 120Brix during the duration of storage. The microbiological load of the samples stored at chilled condition increased gradually from 48 CFU/ml to 2.9 x 105 CFU/mL, while juices stored at ambient condition increased during the first 3 days of storage from 48 CFU/mL to 6.1 x 105 CFU/ml and decreased to 1.2 x 105 CFU/mL after storage period. The over-all acceptability test showed that juices stored at chilled condition acquired higher degree of liking with "Like Moderately" compared to juices stored at ambient condition. The consumer testing revealed that 52% of the consumers would buy the product if it is conveniently available. Thus, further improvement of the juice is recommended for higher consumer acceptance.